Sensitivity of Natural Frequencies to Composite Effects in Reinforced Concrete Elements - Razak, H.A.; Fayyadh, M.M. (2013)
This article attempts to explain the effect of composite action in reinforced concrete (RC) elements on the natural frequencies. Natural frequencies are governed by the relationship between the physical properties of RC elements and its composite action. The softening of concrete in tension, compression, and pre- and post-yielding steel behavior are considered. The bonding action between steel and concrete under loading and unloading conditions is also taken into account. The assumption of the increase in stiffness of RC elements in tension due to bond action is investigated by tests on two RC beams. Both static and modal testing were carried out after inducing different levels of damage in the beams. Results show the validity of the assumption made due to composite action. Mode 1 can be an indicator for bond action behavior and for predicting the yield state of steel in the RC beams. Mode 2 behavior is governed by the amount of steel reinforcement, where for maximum steel ratio it will be affected by concrete softening, while for minimum steel ratio it will be affected by both concrete softening and bond action. Modes 3 and higher can be indicators for concrete softening. Â© 2013 Copyright Taylor and Francis Group, LLC.